An Evaluation of Cybersecurity Risk Management Implementation at Bank Pembangunan XYZ - Ratna Ditha Apsari; Tubagus Muhamad Yusuf Khudri (Greenation Research & Yayasan Global Resarch National, 2025)
Cybersecurity risk management in the financial sector is crucial for mitigating cybersecurity threats. The main objective of this study is to evaluate the implementation of cybersecurity risk management at Bank Pembangunan Daerah XYZ. This research employs a qualitative method with a case study strategy, using primary and secondary data sources through semi structured interviews and surveys conducted with employees and managers of Bank Pembangunan Daerah XYZ. The data is processed using narrative analysis techniques. The findings of this study reveal gaps in the implementation of cybersecurity risk management at Bank Pembangunan Daerah XYZ in accordance with the NIST Cybersecurity Framework, across six components: Govern, Identify, Protect, Detection, Response, and Recovery.